PEMANFAATAN APLIKASI GEOLISTRIK UNTUK IDENTIFIKASI POTENSI AIR TANAH DI DAERAH HILLA - Multi, Warni; Kotarumalos, Sitti Hafsa; Gultom , Rimawanto; Limehuwey, Resti; Patty, Philipus J (Jurnal AbdiMas Nusa Mandiri, 2025)
Hilla, located in Central Maluku Regency, boasts a gently sloping to steep topography. Extensive green plantations dominate the region. However, water resources, a primary need for the community and agricultural land, remain an unresolved challenge. This community service activity was conducted to assess the potential of groundwater in the Hilla area and provide a basis for effective management. Therefore, geophysical applications, specifically geoelectricity, were utilized to identify potential rock aquifers for groundwater storage. The potential aquifer, based on 2D resistivity cross-section data from geoelectrical readings, was identified at the second location, at a depth of 10-15 meters, and is thought to be formed by sedimentary limestone. This interpretation offers valuable insights for the Hilla community and local government to explore and utilize groundwater resources in the surrounding area. Another positive impact is that the Hilla area can meet its need for reliable and economical groundwater sources directly within its own region, without requiring supply from nearby areas or cities. This ensures that the local community's daily activities are effectively met.